2015
DOI: 10.1016/j.jmb.2014.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Model for the Architecture of Claudin-Based Paracellular Ion Channels through Tight Junctions

Abstract: Claudins are main cell-cell adhesion molecules of tight junctions (TJs) between cells in epithelial sheets that form tight barriers that separate the apical from the basolateral space but also contain paracellular channels that regulate the flow of ions and solutes in between these intercellular spaces. Recently, the first crystal structure of a claudin was determined, that of claudin-15, which indicated the parts of the large extracellular domains that likely form the pore-lining surfaces of the paracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
282
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(334 citation statements)
references
References 33 publications
36
282
0
2
Order By: Relevance
“…In the present study, we electrophysiologically determined that claudin-21 forms a charge-selective and size-restrictive pore for small cations. The recently determined structure of claudin-15, analyzed by X-ray crystallography at a 2.4-Å resolution, indicates that the paracellular pathway is formed by the claudin's extracellular domain (25,26). The surface distribution of the electrostatic potential at claudin-21's pore region has a negative charge, which would cause its pore to be attractive for cations but repulsive for anions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we electrophysiologically determined that claudin-21 forms a charge-selective and size-restrictive pore for small cations. The recently determined structure of claudin-15, analyzed by X-ray crystallography at a 2.4-Å resolution, indicates that the paracellular pathway is formed by the claudin's extracellular domain (25,26). The surface distribution of the electrostatic potential at claudin-21's pore region has a negative charge, which would cause its pore to be attractive for cations but repulsive for anions.…”
Section: Discussionmentioning
confidence: 99%
“…Two categories of claudins have been proposed, namely, the paracellular barrier type and the paracellular channel type, based on the transepithelial electrical resistance (TER) or on the cation and/or anion permeability of many epithelial cell lines (5, 7). Among some claudins characterized as channel-type claudins, such as claudin-2, -7, -10, -15, -16, and -17, claudin-2 and -15 have been studied extensively with respect to specific ions and water (9-11, 14, 17, 20, 21, 23, 24).The structure of claudin-15 was recently analyzed; this analysis revealed that two extracellular segments form a unique ␤ sheet domain fixed to a transmembrane four-helix bundle by a W-LW claudin consensus motif (25,26). The high-resolution structure of claudin-15 suggests that a ␤-barrel pore created by eight claudin molecules in the region between two cells can form a paracellular channel, which is regulated by charged residues on the claudins' extracellular domains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For other channel-forming claudins, the ions could potentially also pass a [25] with antiparallel cisarrangement of two linear cis-polymers of claudin protomers. Protomer surfaces are shown either in sky blue or for different regions in blue (TMs), green (ECL1), cyan ECL2, orange (TM1 end), or magenta (TM4 end).…”
Section: Discussionmentioning
confidence: 99%
“…Using PyMOL (version 1.5.0.4 Schrödinger, LLC), the residues mutated in this study were mapped on the model. For generation of a basic schema of the potential architecture of the polymeric TJ strand, the double row model of Cldn15 TJ strands [25] was built and modified by manual positioning of the protomers using PyMOL. Electrostatic potentials were calculated and displayed as potentials on the solvent-accessible surface using the Adaptive Poisson-Boltzmann Solver (APBS, MG Lerner and HA Carlson.…”
Section: Structural Modeling Of Cldn17mentioning
confidence: 99%